Behavioral syndrome in a native and an invasive hymenoptera species. (20th August 2014) - Monceau, Karine; Moreau, Jérôme; Poidatz, Juliette; Bonnard, Olivier; Thiéry, Denis
Abstract Recent studies have focused on the role of behavior in biological invasions. Individuals may differ consistently in time for several behavioral traits (personality) which covary (behavioral syndrome) resulting in different behavioral types, some of them favoring invasion. Social hymenopterans have a strong potential to be invaders and their success depends primarily on the foundresses' ability to found viable colonies. They are expected to be active, explorative and bold for optimally establishing their nest. In Europe, 2 hornet species coexist: the native Vespa crabro and the invasive Vespa velutina. These 2 species may compete for nesting sites and we suggest that the initial success of V. velutina has been favored by its behavior in outperforming V. crabro for the traits involved in nest initiation. Here, we (i) defined the personality of V. crabro and V. velutina, (ii) tested for the existence of behavioral syndrome in these species, and (iii) compared their performances using an open‐field test. Our results show that V. crabro foundresses behave consistently but not V. velutina; this lack of consistency being mainly due to reduced variance among individuals. This result questions the possibility of detecting consistent behavioral differences in species having recently undergone a strong bottleneck. Both species exhibit the same correlations between activity, boldness and exploration and V. velutina clearly outperforms V. crabro for all traits. Our results suggest that activity, boldness, and exploration are implicated in both hornet nest initiation and invasion process which contributed to explain why social hymenopterans are so successful at colonization.